Effect of Adding Al2O3 on Some Physical Properties of the Ceramic Compound - Mahdi, Shatha Hashim; Saad.K.A; Ulvi Kanbur (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Zerlokh bentonite is the main material for preparing ceramic specimens with Al2O3 additions. X-ray diffraction analyses were carried out on the raw material at room temperature. The specimens of additions that could stand up to 1250 ºC are stable. That is shown by analyzing the X-ray diffraction pattern after heat treatment of the specimens. The growth of new phases like cordierite, anorthite, and cristobalite has the highest percentage ratio of cordierite (76.43%) and mullite (40.28%). So the presence of refractory materials in the obtained samples strongly supports the possibility of using bentonite with additions in the ceramics industry for high temperatures. Therefore, it gave distinct physical and thermal structural properties to the new product. The apparent porosity (A.P.) presented decreases with increasing ratios, and the lowest value for the ratio at 1.5% equals 1%. In studying the thermal conductivity coefficient, the thermal conductivity coefficient increased due to a decrease in ratios. The best values for the thermal conductivity coefficient at 1.5% were (0.045 W/m. °C).